2017
DOI: 10.1038/leu.2017.328
|View full text |Cite
|
Sign up to set email alerts
|

Defining the molecular basis of oncogenic cooperation between TAL1 expression and Pten deletion in T-ALL using a novel pro-T-cell model system

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is caused by the accumulation of multiple mutations combined with the ectopic expression of transcription factors in developing T cells. However, the molecular basis underlying cooperation between transcription factor expression and additional oncogenic mutations in driving T-ALL has been difficult to assess due to limited robust T-cell model systems. Here we utilize a new ex vivo pro-T-cell model to study oncogenic cooperation. Using a systems biological approach we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 39 publications
5
32
0
Order By: Relevance
“…Interestingly, we found that STAT5 could bind near the MCL1 gene, albeit without leading to its transcriptional activation (supplemental Figure 4), which is in agreement with the fact that IL-7 does not upregulate Mcl-1 protein in these cells (supplemental Figure 6). Genes upregulated by IL-7 in a STAT5-dependent manner in TAIL7 cells include HRH2, APOL4, and CA6, as well as, expectedly, OSM, IKZF4, PIM1, SOCS2, and CISH, [45][46][47][48][49] whereas among the top downregulated genes, we found BCL6, NLRP6, and IL10 ( Figure 5D; supplemental Figure 4). We validated these results by qPCR analysis of IL-7-treated TAIL7 cells in the presence or absence of S5i.…”
Section: Il-7-stimulated Stat5-dependent Transcriptional Network Anamentioning
confidence: 81%
See 1 more Smart Citation
“…Interestingly, we found that STAT5 could bind near the MCL1 gene, albeit without leading to its transcriptional activation (supplemental Figure 4), which is in agreement with the fact that IL-7 does not upregulate Mcl-1 protein in these cells (supplemental Figure 6). Genes upregulated by IL-7 in a STAT5-dependent manner in TAIL7 cells include HRH2, APOL4, and CA6, as well as, expectedly, OSM, IKZF4, PIM1, SOCS2, and CISH, [45][46][47][48][49] whereas among the top downregulated genes, we found BCL6, NLRP6, and IL10 ( Figure 5D; supplemental Figure 4). We validated these results by qPCR analysis of IL-7-treated TAIL7 cells in the presence or absence of S5i.…”
Section: Il-7-stimulated Stat5-dependent Transcriptional Network Anamentioning
confidence: 81%
“…63 In T-ALL, IL-7 rapidly activates PI3K/Akt, MEK/ERK, and JAK/STAT pathways, 1,17,18,64 which contrasts with the heterogeneous ability of IL-7 to activate MEK/ERK pathway, and the delayed kinetics of Akt activation, in normal T-cells. 48,65,66 In fact, all 3 pathways are activated not only by IL-7 binding to its receptor, leading to heterodimerization of IL-7Ra with gc chain, 1,64 but also by mutational activation of IL-7Ra, which occurs in 9% to 10% of T-ALL cases, relies on receptor homodimerization, and does not require the ligand. 20,[67][68][69] We previously showed that MEK/ERK pathway is dispensable for IL-7-induced viability, growth, or proliferation of T-ALL cells cultured in vitro, 17 whereas PI3K/Akt signaling plays a critical role in mediating IL-7 proleukemia effects.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that PTEN and PTPN2 pathways could be functionally incompatible, as recently demonstrated for TAL1 and IL7R/JAK-STAT signaling cascades. 33 Functional experiments are needed to understand the mutual exclusion of these 2 phosphatase alterations in T-ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent genomic studies have provided a comprehensive catalog of chromosomal and genetic abnormalities involved in T-ALL, including mutations of epigenetic regulators (e.g., PHF6, EZH2, SUZ12), the PI3K-PTEN-AKT pathway (e.g., PTEN, PIK3R1), the JAK-STAT pathway (e.g., JAK3, IL7R), ribosomal genes (e.g., RPL10), USP7, BCL11B, and NRAS genes, for example [35,36]. It should be noted that although it is not exclusive, some of these abnormalities are more frequently found in specific subgroup(s) of T-ALL (e.g., PTEN mutations in TAL-positive cases) [35,37,38], suggesting a potential collaborating effect between type A and type B abnormalities. Please also refer to several recent review articles for more details regarding genetic abnormalities [24][25][26].…”
Section: Molecular Pathogenesis Of Leukemia and Stem Cellsmentioning
confidence: 99%
“…Additionally, recent genome-wide studies have revealed that several genes are more frequently mutated in the TAL1positive T-ALL subgroup than in other subgroups [35]. For instance, mutations in the genes mediating the PI3K-PTEN-AKT-mTOR pathway, including PTEN, are observed in approximately half of TAL1-postive human T-ALL cases [35,37,38], while these mutations are less frequently found in TAL1-negative cases. This finding suggests potential collaborating effects or a requirement of this pathway and could also coincide with the fact that TAL1 affects the mTOR pathway in normal HSCs via the repression of DDIT4 [53].…”
Section: Collaborating Oncogenic Pathways Of Tal1mentioning
confidence: 99%